From education to working life : the labour market outcomes of vocational education and training - (:unkn) unknown (Publications Office of the European Union, 2012)
"While considerable empirical evidence exists concerning the effectiveness of education in general, there has been less emphasis on understanding, from a comparative European perspective, the effect of the type of education on labour market outcomes of young people. Using data from the EU Labour Force Survey 2009 ad hoc module, this report focuses on the labour market outcomes of VET. Comparing levels and orientations of education, it considers employment, occupation or sector differences, the education-to-work transition process, job quality and the effect on wages. The report underlines that initially VET results in positive labour market outcomes, which should bei placed in a longer-term context, given the effect that structural changes in European Union labour markets will have on the demand for occupations in different sectors." (Hrsg., BIBB-Doku)
Keywords: G 1.3.2.2.3 Zweite Schwelle, in Arbeit; G 1.2 Arbeitsmarkt; I 2.2 Europa; Berufseinmündung; Zweite Schwelle; Ausbildungsabschluss; Beschäftigungsfähigkeit; Beruf; Wirtschaftszweig; Einkommen; Internationaler Vergleich; Europa